Black salve: risky escharotic - Natalie Rosario; Juan F Castro (SAGE Publishing, 2022)
Introduction Black salve ointments are variable in their composition with no standard formula. Patient's may turn to unregulated products to self-treat their conditions. Products that are accessible without a prescription are not necessarily safe and may pose risk to those who use them, as in this case with the use of black salve ointment. Methods This case report discusses the use of black salve ointment on a nodular neck cyst in a 55-year-old Hispanic male patient. The patient applied the black salve ointment (Two Feathers Healing Ointment®) to the cyst, where the ointment remained in contact with his skin for seven days. He required oral antibiotics and was referred to wound care for follow up. Discussion After close follow up and treatment with antibiotics, the eschar healed and left a concave scar on his neck with no other observed complications. Conclusion Healthcare providers are encouraged to discuss complementary and alternative medicine options with patients as some may lead to dangerous effects. Lay Summary This is a case report about a 55 year old male patient who used an over the counter product called Black Salve to treat a cyst on his neck. He came to his primary care doctor's office for a usual checkup. Just before leaving his appointment, he mentioned a dark discolored area on his neck appeared after applying the black salve ointment. The black salve caused his skin to break down, get infected, and turn black. He was treated with antibiotics and close follow up care. After the wound healed, he was left with a scar on his neck from where the ointment broke down the skin. Since this product is available without a prescription, it is important that consumers know that it is not safe for use and may cause complications. If in doubt, ask a healthcare provider about a products risks before use.